Torsional oscillation damping in wind turbines with virtual synchronous machine‐based frequency response. Issue 7 (1st March 2022) - Lu, Liang; Saborío‐Romano, Oscar; Cutululis, Nicolaos A.
Abstract: In the quest of improving the frequency response capability of wind turbines, control solutions trying to emulate synchronous machines have been proposed. While their performance in terms of frequency support is relatively good, they may trigger torsional oscillations, cause fatigue and damage in the drivetrain, and reduce its lifetime. In this paper, the torsional oscillations caused by a virtual synchronous machine (VSM)‐based frequency controller are illustrated, and methods for damping them are introduced. Two torsional oscillation damping methods are compared and combined to derive an improved method. Dynamic simulation results show better damping performance from the combined damping method.